Pengetahuan Dan Sikap Perawat Dalam Menggunakan Alat Pelindung Diri (APD) Dengan Kejadian Kecelakaan Kerja di RSUD Dr. R. Koesma Tuban - Apriyanto, Willy Ikhwan; Su’udi, Su’udi; Sumiatin, Titik (Peneliti.net, 2024)
Program hospital safety and health designed to guarantee the safety of nurses from injury or illness at work by complying with laws and regulations hospital safety and health. However, there is still low commitment from nurses who have not implemented the program hospital safety and health well.Correlation analytic research design with approach Cross sectional. The research population was nurses in the inpatient room of dr. R. Koesma Tuban, totaling 98 nurses. The sampling technique used is Total Sampling. How to collect data with a questionnaire in the form google form then data processing is carried out and tested using a test Spearman Rank Correlation. The results showed that the majority (79.6%) of nurses had good knowledge, half had negative attitudes (51.0%) and most had experienced work accidents (58.2%). After doing the test Spearman Rank Correlation obtained p = 0.000 with p <0.005 indicating a strong significant relationship between nurses' knowledge in using PPE and the incidence of work accidents (0.404). There is a strong significant relationship between the attitude of nurses in using PPE and the incidence of work accidents (0.632) with the result p = 0.000 with p <0.005.To reduce the incidence of work accidents, namely by increasing the self-awareness of nurses in using PPE in accordance with standard operating procedures, training hospital safety and health such as socialization and workshop and motivate nurses to always apply safety behavior.